DEVELOPMENT OF MICROPLASTIC POLLUTION AWARENESS SCALE FOR PROSPECTIVE SCIENCE AND BIOLOGY TEACHERS - Güleşir, Tuğçe; Gül, Ali (International Online Journal of Education and Teaching, 2022)
The objective of this study is to develop a scale to measure science and biology teacher candidates' awareness of micro-plastic pollution. The sample group consists of 586 participants from 4 universities who are currently enrolled in science and biology teaching programmes. “Microplastic Pollution Awareness Scale (MPAS)" used as data collection tool developed by the researcher. EFA was applied to the data obtained from the application, it was determined that the scale had a 3-factor structure, and that the factors made up 49.57% of the total variance in general. DFA was applied to verify the obtained factor structure. According to the DFA results; χ2/df is perfect harmony; RMSEA, SRMR, CFI, GFI and NNFI are good/perfect harmony; AGFI and NFI are acceptable harmony. The overall reliability coefficient of the scale was determined as 81, the value of which is considered to be of high level reliability. MKFÖ, which is a likert scale, consists of a total of 14 items, including 5 negative and 9 positive items. The maximum score that can be obtained from the scale is determined as 28, and the score obtained from the scale is in direct proportion with the level of awareness of the individual about microplastic pollution.